Denah Rumah sebagai Simbol Konflik dan Relasi Kuasa dalam Novel Teka-teki Rumah Aneh (Henna Ie) - Alamanda Hesarianti; Nina Alia Ariefa (Universitas Al Azhar Indonesia, 2026)
This study examines the representation of family conflict in Teka-teki Rumah Aneh (Henna Ie) by Uketsu. Unlike previous studies that emphasize psychological conflict, this research focuses on how conflict is constructed as a generational power relation and materialized through domestic spatial configuration. The study aims to analyze how power operates within parent–child relations by integrating the sociology of literature, symbol theory and spatial studies. This research employs a Qualitative Textual Analysis of Narrative Descriptions, spatial configurations, and genealogical discourse in the novel. The findings reveal that family conflict is not primarily expressed through explicit dialogue, but through structural mechanisms such as spatial isolation, control of visibility, genealogical exclusion, and succession pressure. The house plan functions as an ideological device that regulates mobility, determines visibility, and reproduces generational hierarchy. Elements such as windowless rooms, concealed spaces, and inherited architectural design demonstrate how domestic space operates as a medium of control and exclusion. The novelty of this study lies in conceptualizing domestic space as a narrative mechanism that materializes structural family conflict. Theoretically, this study proposes the notion of “spatialized generational power relations,” highlighting how architecture in contemporary Japanese literature serves as a site where traditional genealogical norms and individual autonomy are continuously negotiated.Keywords - Domestic Space, Family Conflict, Generational Power Relations, Ie System, Spatial Narrative.